Impact of Air Pollutant on Heart Rate Variability in Healthy Young Adults - Melinski, Anita de Cássia; Catai, Aparecida Maria; Moura, Sílvia Cristina Garcia de; Milan-Mattos, Juliana Cristina [UNESP]; Takito, Monica Yuri (Sociedade Brasileira de Cardiologia, 2022)
Background: Air pollution and sex independently affect cardiac autonomic control, which can be assessed by heart rate variability (HRV). The research hypothesis is that individuals exposed to low concentrations of pollution have higher cardiac autonomic modulation compared to those exposed to high concentrations and that women have better cardiac autonomic control than men. Objective: To analyze the impact of exposure to air pollutants, specifically smoke, and sex on HRV in healthy young people exposed to different concentrations of pollution over an average period of 22 years. Methods: From April to September 2011, 36 participants of both sexes (20-30 years old) were selected, grouped by levels of air pollution exposure according to indices provided by the Environmental Company of São Paulo State. The R-R intervals (R-Ri) of the electrocardiogram were captured using a heart rate monitor during supine rest. HRV was analyzed by spectral analysis and conditional entropy. The Queen´s College step test was used to characterize functional capacity. A between-group comparison was performed using the two-way ANOVA statistical test (post hoc Tukey) and p<0.05. Results: Significant differences were found in mean R-Ri (p<0.01) and cardiac parasympathetic modulation between sexes in the same city (p=0.02) and between groups exposed to different air pollution concentrations (p<0.01). Conclusion: Our results suggest that long-term exposure to air pollutants, specifically smoke, has an unfavorable impact on HRV, with reduced cardiac vagal autonomic modulation in healthy young adults, especially females.
Keywords: Air pollution; autonomic nervous system; heart rate; sex